2020
DOI: 10.33549/physiolres.934615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods used for evaluation of mutagenicity/genotoxicity of model chemicals - parabens

Abstract: Growing worldwide efforts to replace (reduce) animal testing and to improve alternative in vitro tests which may be more efficient in terms of both time, cost and scientific validity include also genotoxicity/mutagenicity endpoints. The aim of the review article was to summarize currently available in vitro testing approaches in this field, their regulatory acceptance and recommended combinations for classification of chemicals. A study using the combination of Comet Assay performed on two cell lines and the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
7
0
1
Order By: Relevance
“…The determination of the possible genotoxic potential of a chemical compound is an essential part of a toxicological evaluation. Currently, genotoxicity testing is performed using a battery of in vitro or in vivo tests [ 1 , 32 , 33 , 34 , 35 , 36 ]. The need for a test battery for genotoxicity arises from the limitations of individual test systems, as no single test is capable of detecting all genotoxic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the possible genotoxic potential of a chemical compound is an essential part of a toxicological evaluation. Currently, genotoxicity testing is performed using a battery of in vitro or in vivo tests [ 1 , 32 , 33 , 34 , 35 , 36 ]. The need for a test battery for genotoxicity arises from the limitations of individual test systems, as no single test is capable of detecting all genotoxic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach [111,112,126] is based on the use of such test systems as: 1) Bacterial Reverse Mutation Test (TG471); 2) In vivo test for detection of mammalian erythrocyte micronuclei (TG473); 3) Unscheduled DNA Synthesis (UDS) Test (TG486) or In Vivo Mammalian Alkaline Comet Assay (TG489). The most common methods for assessing genotoxic potential include Bacterial Reverse Mutation Test (TG471), In Vitro Mammalian Cell Micronucleus Test (TG487) and In Vitro Mammalian Chromosomal Aberration Test (TG473) [68].…”
Section: Genotoxicity Assessment Methodsmentioning
confidence: 99%
“…To date, the main obstacle to solving this problem is the lack of free access to information on more than 50,000 chemicals, as such information is considered confidential [67]. In addition, for a large number of chemicals, experimental toxicological data are limited [36,68], making it impossible to use classical in vitro approaches to assess the genotoxicity of these chemicals [68]. In everyday life, the human hereditary apparatus is exposed to a large number of external DNA-damaging chemical agents [16,41,59].…”
Section: Exogenous Factorsmentioning
confidence: 99%
“…Although parabens have a long history of use and are generally considered safe and low in toxicity, their effects on the health of organisms are gradually being reported [11]. Several recent in vivo studies have shown that parabens have the ability to accelerate ovarian aging, impede embryo implantation in mice, and interfere with epigenetic regulation in humans and rodents, and may cause reproductive toxicity and genotoxicity [12][13][14][15]. Further epidemiological investigations have found that parabens have weak estrogenic activity and can disrupt sex hormone levels in the body [16], even affecting prenatal fetal and child development and increasing the risk of breast cancer in women [17][18][19].…”
Section: Introductionmentioning
confidence: 99%